Education in Safe and Unsafe Spaces - Callan, Eamonn (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2016)
Recent student demands within the academy for "safe space" have aroused concern about the constraints they might impose on free speech and academic freedom. There are as many kinds of safety as there are threats to the things that human beings might care about. That is why we need to be very clear about the specific threats of which the intended beneficiaries of safe space are supposed to be relieved. Much of the controversy can be dissolved by distinguishing between "dignity safety," to which everyone has a right, and "intellectual safety" of a kind that is repugnant to the education worth having. Psychological literature on stereotype threat and the interventions that alleviate its adverse effects shed light on how students’ equal dignity can be made safe in institutions without compromising liberty. But "intellectual safety" in education can only be conferred at the cost of indulging close-mindedness and allied vices. Tension between securing dignity safety and creating a fittingly unsafe intellectual environment can be eased when teaching and institutional ethos promote the virtue of civility. Race is used throughout the article as the example of a social category that can spur legitimate demands for "dignity safe space."